Physical Culture and Sports in the USSR and Soviet Kazakhstan in 1940-1980 - Galimzhanovna Saktaganova, Zauresh; Anatolievich Grigorkevich, Aleksandr; Sabitbekovna Mazhitova, Zhanna; Serikovna Sagatova, Assem; Suyundykovna Kassimova, Saule (Opción, 2019)
The present article considers the problems of physical culture and sports in the Soviet history. It emphasizes the fact that physical culture and sports had a complicated history. In the pre-war period, sports were considered to serve a narrow utilitarian purpose of establishing healthy society via doing exerci- ses and training bold fighters for the bright new dawn of communism. Later, sports were perceived as one of the key components of social and political life – an effective means to increase labor productivity and bring up a stron- ger next generation. Analyzing the government actions on establishing sports infrastructure, the authors conclude that physical culture and sports in the USSR and Soviet Kazakhstan transformed into an independent area of cultural development. The conclusion states that high achievements in conventional sports were to prove the benefits of living in a socialist country to its citizens and the rest of the world. In turn, such a circumstance led to the disregard of sports peculiarities of Kazakhstan and the gradual fallback of national sports.